EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHCardiac stem and progenitor cells as a potential therapeutic agent for the treatment of damaged cardiac muscle - Wilczek, Piotr Michał; Zembala, Marian; Zembala, Michał; Mzyk, Aldona; Cichoń, Tomasz; Smolarczyk, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Specific cardiac stem cells/progenitor cells (CSCs/CPCs) are multipotent and clonogenic, giving rise to cardiomyocytes, smooth muscle cells and endothelial cells. These cells can be used in cell therapy for the treatment of diseased heart tissue, but there is a need for an effective isolation process, and characterization of the phenotype and morphology of the isolated cells, to increase the potential therapeutic use of this type of cells. Aim of the stud y: The aim of this study was to isolate the CSCs/CPCs from the tissue fragments derived from explanted heart, and characterize the phenotype and morphology of the isolated cells. Material and methods : Myocardial tissue samples were taken from explanted hearts under sterile conditions. After the cells had grown to confluence, they were detached by gentle enzymatic digestion and seeded on poly-D-lysine-coated dishes. Using flow cytometry methods the phenotype of the isolated cells was analyzed. Applying phase contrast and fluorescent microscopy techniques the morphology of the cells and growth characteristics were evaluated. Results: The isolated cells showed the CSCs/CPCs phenotype expressing the c-kit receptor, Nkx 2.5, MDR-1, and GATA-4. The cells were also positive for mesenchymal stem cell receptors including CD90, CD105, CD73 and CD144. Only a few cells were positive for the Lin-1, Lin-2 and Lin-3 receptors. The growth characteristics and cell morphology differ depending on the place of isolation. Conclusions : The CSCs/CPCs seems to have a great therapeutic potential, but there is a need for a full description of phenotype, morphology and growth characteristics.